Análisis de la información que publica la sección de ciencia y tecnología del diario El Comercio. - Cruz Zambrano, Stalin Daniel (2013)
The present studyaims to analyzewhether the informationthatis published in thejournalsectioncommercetechnology, meetwriting standardsrequired for the preparationof topicsrelating toscience and technology.To do this,in the first andsecond chapter hasconsidered takinginto account the conceptsofscience, society andcommunication, and in this wayunderstand its meaning. In the thirdchapterdevelopsthe conceptsand definitionsof journalism.Also,there is a briefreviewof theSpecialized Journalismas an introductionto the main theme: ScientificJournalism. This sectionends withthe relationshipbetween scienceand journalism.